Comparative Characteristics of Antioxidative Enzymes of Yersinia pestis Strains of Different Subspecies and Yersinia pseudotuberculosis Strains - N. A. Vidyaeva; A. V. Gaeva; L. M. Koukleva; G. N. Odinokov; V. V. Kutyrev (Проблемы особо опасных инфекций, 2008)
Comparative electrophoretic investigation was carried out to study antioxidative enzymes (superoxide dismutase, catalase and peroxidase) in strains of Yersinia pestis, Yersinia pseudotuberculosis, Escherichia coli and Salmonella typhimurium. It was shown that Yersinia antioxidative enzymes are different from E. coli and S. typhimurium enzymes in electrophoretic motility. Their expression depends on cultivation temperature and plasmid content. Peculiarities of catalase-peroxidase expression were determined in strains of plague etiological agent of Ulegei subspecies, in strains of pseudotuberculosis etiological agent of IV serovar and in strains isolated from humans.